ChemInform Abstract: Pd‐Catalyzed Asymmetric Suzuki—Miyaura Reactions Using Chiral Mono‐ and Bidentate Phosphorus Ligands. Issue 4 (28th January 2014) - Balanta Castillo, Angelica; Perandones, Bernabe F.; Zangrando, Ennio; Gladiali, Serafino; Godard, Cyril; Claver, Carmen
Abstract A series of monodentate and bidentate chiral phosphorus based ligands including carbohydrate‐derived diphosphites are tested in the asymmetric Suzuki coupling of aryl halides with 1‐naphthylboronic acids.